Kesenian Indonesia - M. Junus Melalatoa (Antropologi Indonesia, 2000)
Art presents a discursive space for thought and affect that is part of the cultural configuration of a society. Thus defined, an assumption is made that Indonesia possesses no discursive space for the 200 million people that make up its pluralistic society, if traditional art presents space only for the bearers of that tradition. There are many who say that 'Indonesian' art has already emerged, and provide examples from various art forms. Furthermore, there is the notion that traditional art is generally static, inferior, unbefitting and unable to fulfill the needs of 'modern' Indonesians-especially going into the 21st century. In fact, traditional art continues to undergo shifts and changes, or to disappear as a discursive space with any significance. While holding to the assumption mentioned above, this article seeks an understanding of traditional art extant in the ethnic groups that comprise Indonesia's pluralistic society. The question is whether the Indonesian people see themselves as heirs to the various traditional art forms, or whether such art can serve as a vehicle for social integration in Indonesia.